Chemical composition, lipid peroxidation, and fatty acid profile in meat of broilers fed with glycerol monolaurate additive. (15th November 2020) - Valentini, J.; Da Silva, A.S.; Fortuoso, B.F.; Reis, J.H.; Gebert, R.R.; Griss, L.G.; Boiago, M.M.; Lopes, L.Q.S.; Santos, R.C.V.; Wagner, R.; Tavernari, F.C.
Abstract: The objective of this study was to evaluate the chemical composition and fatty acid profile of broilers fed diets containing glycerol monolaurate (GML) in place of antimicrobials. Groups: T0 group used as control; T100, T200, and T300 groups received diets supplemented with 100, 200, and 300 mg/kg of GML, respectively. The feed mixture used in the poultry feed during the four phases of the production cycle (days 1 to 7; 8 to 21; 22 to 35; and 36 to 42 of birds age) showed similar levels of protein, lipid and ash, as well as fatty acid profiles. Samples of frozen breasts from chickens slaughtered at 42 days of age were used for chemical gross composition and fatty acid analysis. We observed lower lipid levels in the meat of broilers in the T200 and T300 groups than in the T0 group. Lower lipid peroxidation occurred in the meat of animals that consumed GML in respect to control. Total saturated fatty acid percentage was lower, while total polyunsaturated fatty acid percentage was higher in the meat of broilers fed GML than in the control group. We conclude that the increase in GML concentrations alters the lipid profile of broiler meat.